RE - Fernández-Vílchez, Iliana (Instituto Tecnológico de Costa Rica, 2017)
Public universities of Costa Rica look for a continuous improvement in education, within this aspect, investing in regional headquarters is important to ensure accessibility to the entire population with intentions of overcoming. The professional reason of this project has relevance in the construction of student residences in regional areas of the country, as part of a process of equal access to education. The number of students enrolled is increasing at the regional headquarters, which leads to a response, through the program of residences, spaces and services suitable for students from distant places from the study centers. In this final graduation paper, the possibility of improving the conditions of students’ residences at the Golfito Campus of the University of Costa Rica is proposed, as well as a proposal for a functional plan as part of the continuous improvement. On the other hand, the structure of the document is through the project process which starts with the assignment, which explains the need of the project and the request made by the client. Subsequently it is divided in 6 phases: data, information, problem, intention, proposal and materialization. In the data phase, data are selected to understand in a global way where the project will be located, as well as the functionality of the project. In the information phase, the data are organized into four blocks, from which urban approaches and guidelines for the architectural proposal are generated. The problem phase consists of the definition of the problema with which an architectural program is established, with areas recommended to establish a design of residences. On the other hand, it defines the structure of the problema and the diagram of functional relations, both guides for the design process. The intention phase determines the base volumetry and the intentions to attend, which starts the next phase of the proposal, where the problem is solved at architectural, functional and urban level. This ends with the evaluation of the project, in the materialization phase. In this phase the technical development of the proposal must be incorporated, however, the scope of this research is at the preliminary project level, so the technical part is executed only if the project is concrete. Finally, conclusions and general recommendations based on the research and the project itself are included.
residencias estudiantiles del Recinto de Golfito de la Universidad de Costa Rica
Proyecto de graduación (Licenciatura en Arquitectura y Urbanismo) Instituto Tecnológico de Costa Rica, 2017.
Keywords: Residencias estudiantiles; Diseño arquitectónico; Arquitectura